Comprehensive Language and immediate memory in students of 5th and 6th grade of elementary school from rural and urban area of Lima - Matalinares Calvet, María (2007)
This research had as propose establish if it existed or not relatioship between Comprehensive Language and Immediate Auditory  Memory in Primary School Pupils of the 5.° and 6.° grades of rural and urban zones from Lima.